Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages CONTENTS (continued) PAGE 3. ACCIDENTS ........................14 Training in Safety Methods ............14 Safety Committees .. .. .. .. ..13 Fencing and Guarding Machinery .. .. 16 Hoists, Lifts, Chains, and Ropes .. .. .. 17 Cranes and Lifting Machines ............17 Weight Lifting .. .. .. .. .. 17 Eye Injuries .. .. .. .. .. 19 Treatment of Accidents................20 First Aid .. .. .. .. .. .. 20 Notifying Accidents and Diseases............21 Compensation for Injuries .. .. .. .. 21 Special Reguladons .. .. .. .. .. 23 4. HOURS OF WORK ....................23 Hours of Women and Young Workers .. .. 23 Rest Pauses .. .. .. .. .. .. 27 5. FILLING FACTORIES ....................27 Cleanliness .....................29 Education........................30 Selection of Workers .. .. .. .. 30 Investigation of Absenteeism .. .. .. 30 Diet............................30 6. FACTORY MEDICAL SERVICE ............31 What a Health Department Can Do .. .. 33 Health Records .. .. .. .. .. 33 7. HOW WORKERS CAN TACKLE HEALTH PROBLEMS Organize for Health on the Job............33 Enforcing the Law....................36 How to Approach the Factory Inspector .. .. 37 What to do if You are not Covered by the Factories Act............................37 The Trade Unions and Health Matters .. .. 37 L.R.D. Industrial Health Committee .. .. 38 APPENDIX I Dangerous Trades Regulations............39 Trades covered by Welfare Orders .. .. 39 APPENDIX II Publications on Health in Industry .. .. 40 21/2049